Letter from Rosa and Georg Bredig to Max Bredig, May 22, 1928 - Bredig, Rosa; Bredig, Georg (1928)
Georg Bredig (1868-1944) provides substantial professional advice to his son, Max Bredig (1902-1977). The letter is transcribed by Rosa Bredig (1877-1933).
Keywords: Bredig, Rosa, 1877-1933; Bredig, Max Albert, 1902-1977; Bredig, Georg, 1868-1944